FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU WUS (USIA 30-50 TAHUN) DALAM MENDETEKSI DINI KANKER LEHER RAHIM MELALUI METODE IVA - Laraswani, Laraswani; Vionalita, Gisely (Universitas Esa Unggul, 2020)
Nationally, cervical cancer is a cancer with the highest prevalence of cancer cases in Indonesia of 0.8%, while Tangerang Regency is at the 8th level of the highest number of PTM cases of 139 cases. The high prevalence of cervical cancer requires efforts to increase early detection such as IVA. But in Sindang Jaya Health Center in 2016 and 2017 there was a decrease in IVA examination visits, from 256 people to 209 people (0.76%), which was less than the national IVA coverage target of 10% of the total WUS at the end of the year. This study aims to analyze the factors associated with the behavior of WUS in early detection of cervical cancer through the IVA method in Sindang Jaya Health Center in 2018. The design of this studi is quantitative research with cross-sectional study design. A population of 68 WUS visited the KB KB every month and the sample used was 49 WUS with a purposive sampling technique. Data were analyzed using the Chi Square test with the results showing that there was a relationship between knowledge (p-value 0.017), information exposure (p-value 0.002), and husband support (p-value 0.037) with IVA check behavior. And there is no relationship between education (p-value 0.316) and attitude (p-value 0.095) with IVA check behavior. Therefore knowledge, exposure to information, and husband's support are needed to improve the behavior of WUS in early detection of cervical cancer through the IVA method.Â Keywords : early detection, IVA, women of childbearing age